ADSORPSI ION LOGAM Pb2+ DAN Cu2+ OLEH BENTONIT TERAKTIVASI BASA (NaOH) - Putu Aprilliana Indah Kumala Dewi; Putu Suarya; James Sibarani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2015)
The aim of this study is to determine the adsorption capacity of NaoH activated bentonites in reducing metal ions Pb2+ and Cu2+ from their solutions. The characterization of the activated bentonites was carried out by determining the specific surface area using methylene blue adsorption method, the numbers of the active site by acid-base titration, and determining the basal spacing using X-ray diffraction (XRD). Adsorption parameters such as contact time, pH, and the isotherm adsorption curves were determined by atomic absorption spectrophotometer (AAS). The specific surface area and the number of active sites of the NaOH-activated Bentonite were 22.1017 m2/g and 32.8716 x 1020 atoms/g respectively. This vakue was higher than non-activated ones which were 12.6602 m2/g and 31.5847 x 1020 atoms/g respectively. The optimum condition of Pb2+ adsorption on activated bentonite was obtained at pH 3 with contact time under 5 minutes following the Langmuir isoterm pattern while the optimum condition of Cu2+ adsorption was obtained at pH 4 with contact time under 5 minutes following the Langmuir isoterm adsorption suggesting that the adsorption took place by chemical adsorption. The adsorption capacities of Pb2+ and Cu2+ were 185.50 mg/g and 30.00 mg/g respectively.